Pengaruh Kinerja Keuangan, Profitabilitas Dan Likuiditas Terhadap Harga Saham Dengan Kebijakan Deviden Sebagai Variabel Moderating Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020 - Syafrin, Indra; Fasridon; Putra, Waldino (Journal of Science Education and Management Business, 2022)
Abstract. This study aims to determine the effect of financial performance, profitability and liquidity on stock prices with dividend policy as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The sample in this study was taken using a purposive sampling technique with a total of 45 companies. The analytical technique used is panel data regression analysis with the help of the E-Views 10 program. The results of this study are that financial performance and liquidity have no effect on stock prices, while profitability has a significant positive effect on stock prices. Financial Performance and Liquidity have a positive and significant effect on Stock Prices through Dividend Policy, while Profitability has a negative and significant effect on Stock Prices through Dividend Policy.